Peripartum Isolated Cortical Venous Thrombosis. Issue 2 (19th September 2014) - Singh‐Kandola, Kiran; Tailor, Neeta; Phillips, Jessica; Collis, Rachel
Summary: We present a rare, and often mis‐diagnosed, case of an isolated cortical venous thrombosis. The consequences of this are potentially severe, and its non‐specific presentation requires a high degree of suspicion. A 26‐year‐old female had had an uncomplicated lower segment caesarean section at term. A combined spinal epidural anaesthetic technique was used and there were no immediate postpartum issues. The patient was readmitted ten days later with a three day history of severe headache and photophobia. CT scan of the brain was normal. On day two she suffered a seizure with residual right sided weakness. MRI scan demonstrated sub‐acute haemorrhage into the subdural space of the left posterior portion of the frontal lobe. A cerebral angiogram revealed delayed filling of the cortical veins of the left parietal lobe. Following treatment there were no neurological sequelae.